Telaprevir in treatment of chronic hepatitis C: safety issues - T. M. Ignatova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze results of controlled clinical studies of efficacy and safety of telaprevir within triple antiviral therapy of chronic hepatitis C (CHC) with evaluation of frequency and spectrum of adverse effects (AE), and also approaches of their management.Original positions. Investigations carried out to the present time demonstrated, that addition of telaprevir to standard therapy by pegilated interferon-alpha and ribavirin increases frequency of achievement sustained virologic response in CHC patients with the 1 genotype of virus almost 2-fold. Tolerability of treatment with addition of telaprevir was satisfactory as a whole; however frequency of skin rashes and pruritus (over 50%), anemia (about 40%) and anorectal symptoms (26%) was higher, than at standard double therapy (placebo group). A little higher frequency of serious AE (7%), cancellation of all drugs due to AE (8%) was observed. Increase of frequency and severity of skin reactions, that was a principal cause of treatment cancellation, is of special importance. AE spectrum at telaprevir application differs from AE spectrum at triple therapy with addition of another new protease inhibitor – boceprevir (predominance of anemia, dysgeusia). Original approach of monitoring and effective management of AE allowed to decrease frequency of cancellation of treatment due to dermal reactions in III phase investigations in comparison to results of II phase studies. Special attention is given to prophylaxis of interactions with other pharmaceuticals, as telaprevir is P450 (СYP) 3A4 substrate and inhibitor and P-glycoprotein transporter.Conclusion. Application of telaprevir within triple therapy of CHC results in change of AE spectrum. The major importance has elevation of frequency and severity of skin reactions. Tactics of early diagnostics, monitoring and active treatment of AE, and drug interactions prophylaxes increase safety and efficacy of treatment.